(untitled) (Nigerian Journal of Technology, 2021)
A simple and elegant impedance-matching method for rectenna operating in a narrow frequency range is presented. The method used two coplanar strip lines emerging from the antenna feed-point, to correct for the reactive component of the antenna impedance on one side, and to connect the rectifier and transform its impedance on the other side. The experimental results were supported by numerical simulations, which suggest that the same impedance matching technique can be used for mm-waves and terahertz (THz) radiation applications. Microwave characterization of the fabricated devices (impedance-matched and non-matched) showed that the responsivity of the impedance-matched rectenna is approaching an order of magnitude higher at 20 GHz than that of a control device without a matching network.